Can BMC be used as Planning Tools for MSMEs to Advance to Class? - Novita, Vivianti; Nurlinda; Rahmadani (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This research aims to prove the importance of MSMEs in designing their business models to achieve the goal of MSMEs moving in class. MSMEs advancement in class is indicated by the increase in turnover and assets owned, so business design becomes a necessity for MSMEs and BMC is one of the simplest and easiest methods that can be used by MSMEs in designing their business models. This research is qualitative. Data collection techniques were carried out using a combination of surveys and interviews. Data analysis uses BMC Tables, SWOT, and description analysis. The research results show that with BMC, MSMEs can find out their ability to achieve the criteria for MSMEs to be promoted to class. The business model shows that MSMEs have moved up a class from the retail market to supermarkets and derivative product markets such as cake shops and bakeries.